Lower lung function associates with cessation of menstruation: UK Biobank data. Issue 5 (22nd September 2016) - Amaral, André F.S.; Strachan, David P.; Gómez Real, Francisco; Burney, Peter G.J.; Jarvis, Deborah L.
Little is known about the effect of cessation of menstruation on lung function. The aims of the study were to examine the association of lung function with natural and surgical cessation of menstruation, and assess whether lower lung function is associated with earlier age at cessation of menstruation. The study was performed in 141 076 women from the UK Biobank, who had provided acceptable and reproducible spirometry measurements and information on menstrual status. The associations of lung function (forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ), spirometric restriction (FVC < lower limit of normal (LLN)), airflow obstruction (FEV1 /FVC <LLN)) with cessation of menstruation and age at cessation of menstruation were assessed using regression analysis. Women who had natural cessation of menstruation showed a lower FVC (−42 mL; 95% CI −53– −30) and FEV1 (−34 mL; 95% CI −43– −24) and higher risk of spirometric restriction (adjusted odds ratio 1.27; 95% CI 1.18–1.37) than women still menstruating. These associations were stronger in women who had had a hysterectomy and/or oophorectomy. The earlier the natural cessation of menstruation, the lower the lung function. There was no clear association of lung function with age at hysterectomy and/or oophorectomy. Airflow obstruction was not associated with cessation of menstruation. Lower lung function associates with cessation of menstruation, especially if it occurs early in life. Low lung function associates with menopause, especially if it occurs early in life http://ow.ly/RWRt3021tBY